2013
DOI: 10.1002/ijc.28309
|View full text |Cite
|
Sign up to set email alerts
|

Tumor‐infiltrating CD14‐positive myeloid cells and CD8‐positive T‐cells prolong survival in patients with cervical carcinoma

Abstract: One of the hallmarks of cancer is the influx of myeloid cells. In our study, we investigated the constitution of tumorinfiltrating myeloid cells and their relationship to other tumor-infiltrating immune cells, tumor characteristics and the diseasespecific survival of patients with cervical cancer (CxCa). Triple-color immunofluorescence confocal microscopy was used to locate, identify and quantify macrophages (CD14), their maturation status (CD33) and their polarization (CD163) in a cohort of 86 patients with c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
98
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 115 publications
(113 citation statements)
references
References 49 publications
7
98
3
Order By: Relevance
“…Deciphering the exact molecular cues responsible for macrophage polarization during treatment seems critical for effective therapy. Recently, we have demonstrated a positive correlation of a dense infiltration of M1-type macrophages with patient survival in a cohort of cervical cancer patients (45), supporting the notion that macrophage skewing toward antitumor activity, rather than macrophage depletion, might be the optimal strategy. Our study illustrates that immunogenic cancer vaccines can be instrumental to induce such a repolarization of intratumoral macrophages.…”
Section: Discussionsupporting
confidence: 55%
“…Deciphering the exact molecular cues responsible for macrophage polarization during treatment seems critical for effective therapy. Recently, we have demonstrated a positive correlation of a dense infiltration of M1-type macrophages with patient survival in a cohort of cervical cancer patients (45), supporting the notion that macrophage skewing toward antitumor activity, rather than macrophage depletion, might be the optimal strategy. Our study illustrates that immunogenic cancer vaccines can be instrumental to induce such a repolarization of intratumoral macrophages.…”
Section: Discussionsupporting
confidence: 55%
“…Tumors with high IL-6 expression displayed a dense infiltration with CD14CCD33¡CD163C cells and CD14CCD33¡CD163C cells, specifically the mature (CD33-) type of myeloid cells. Our observation that the expression of IL-6 was correlated with the presence of CD14CCD33¡CD163-cells, potentially reflecting recent infiltrated monocytes or M1 macrophages, 24 is somewhat counterintuitive. However, as the number of these tumor-infiltrating cells was generally low when compared to other cancer types, 24 and is directly correlated to co-infiltration with much larger quantities of suppressive CD33¡CD163C cells, this association is more likely to reflect that in essence IL-6 expressing tumors induce a hostile tumor immune environment.…”
Section: Discussioncontrasting
confidence: 60%
“…20 Other studies also showed a positive relationship between M1 infiltration and survival. [36][37][38][39][40] Notably, HPV-induced vulvar carcinomas are known for their good overall prognosis and survival rate of approximately 80%.…”
Section: Discussionmentioning
confidence: 92%
“…32,33 Triple immunofluorescent confocal microscopy Simultaneous detection of monocytes was carried out by triple fluorescent staining and confocal microscopy as described previously. 20 In brief, sections were deparaffinized and antigen retrieval was performed in pre-heated Tris-EDTA buffer pH 9.0. Primary antibodies: CD14 (anti-CD14, mouse IgG2a, clone 7; Novocastra 1:50), CD33 (anti-CD33, mouse IgG2b, clone PWS44; Novocastra (1:100) and CD163 (anti-CD163, mouse IgG1, clone 10D6; Novocastra 1:1,600).…”
Section: Patient Materialsmentioning
confidence: 99%
See 1 more Smart Citation